Performance Analysis of a Contra-Rotating Propeller with a Toroidal Blade Model - Muhammad Arju Muhafiz; Fajri Ashfi Rayhan (Applied Science and Technology on Naval Engineering, 2026)
This research analyzes the performance of contra-rotating propellers (CRP) with toroidal blade designs and compares them to conventional CRPs to evaluate propulsion efficiency. The study is motivated by the maritime sector's need for more efficient and reliable propulsion systems. The methodology employed is Computational Fluid Dynamics (CFD) simulation, utilizing variations in RPM (1000–3000) and pitch (228.6–336 mm) to test relevant operational conditions. Key findings indicate that the contra-rotating toroidal propeller generates 16% higher thrust (reaching 3193 N at 3000 RPM) and an average thrust coefficient (KT) of 0.47, which is 17% higher than conventional CRPs. However, the efficiency of the contra-rotating toroidal propeller (average 68,7%) was 9,6% lower than the conventional CRP with a 264 mm pitch (78.31%), despite its superior absolute thrust. Fluid flow contour analysis suggests that the toroidal propeller's circular blade design creates a more stable flow pattern. The significance of this research lies in highlighting the substantial potential of contra-rotating toroidal propellers in boosting propulsion thrust, though further optimization is required for efficiency. These findings underscore the necessity for refining geometric parameters like skew and rake. This study provides a crucial foundation for the development of innovative propellers that combine the advantages of contra-rotating systems and toroidal designs, promoting more efficient and reliable propulsion solutions in the future. Keywords: Toroidal propeller, contra rotating propeller, propulsion efficiency